Islamic Leadership Values: A Conceptual Study - Muhamad Rizky Rizaldy; Maulana Syarif Hidayatullah (Dialogia, 2021)
Leadership is an important aspect of Islam and the lives of its adherents. Therefore, studying and developing leadership concepts in Islam is also a fundamental necessity considering the various contemporary problems that are being faced by the ummah can be seen as a form and consequence of the leadership vacuum. Experiencing Islamic revival in various fields, which is also at the same time dealing with the emptiness of modern life that tends to be value-free, strengthens the urgency of leadership that is in accordance with and able to accommodate the Islamic values of its followers. This paper aims to examine the main sources in the Islamic tradition and contemporary literature related to Islamic leadership in order to map the main leadership values discussed in it, and to present a discourse related to how these values are relevant in various contexts of modern and professional life, especially in filling the void of Islamic leadership in the business context, considering that most of the conceptual literature on Islamic leadership is in the context of political and religious leadership. By studying leadership, leaders in the business sector can avoid the dark sides of leadership that may threaten the sustainability of their organizations.